Peptidomimetic hydroxamate metalloproteinase inhibitors abrogate local and systemic toxicity induced by Echis ocellatus (saw-scaled) snake venom - Arias, Ana Silvia (2017)
The ability of two peptidomimetic hydroxamate metalloproteinase inhibitors, Batimastat and Marimastat, to abrogate toxic and proteinase activities of the venom of Echis ocellatus from Cameroon and Ghana was assessed. Since this venom largely relies for its toxicity on the action of zinc-dependent metalloproteinases (SVMPs), the hypothesis was raised that toxicity could be largely eliminated by using SVMP inhibitors. Both hydroxamate molecules inhibited local and pulmonary hemorrhagic, in vitro coagulant, defibrinogenating, and proteinase activities of the venoms in conditions in which venom and inhibitors were incubated prior to the test. In addition, the inhibitors prolonged the time of death of mice receiving 4 LD50s of venom by the intravenous route. Lower values of IC50 were observed for in vitro and local hemorrhagic activities than for systemic effects. When experiments were performed in conditions that simulated the actual circumstances of snakebite, i.e. by administering the inhibitor after envenoming, Batimastat completely abrogated local hemorrhage if injected immediately after venom. Moreover, it was also effective at inhibiting lethality and defibrinogenation when venom and inhibitor were injected by the intraperitoneal route. Results suggest that these, and possibly other, metalloproteinase inhibitors may become an effective adjunct therapy in envenomings by E. ocellatus when administered at the anatomic site of venom injection rapidly after the bite.